THE LICENSE FOR HIRING FOREIGN WORKERS IN INDONESIA - Ngaisah, Siti (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
The entry of foreign workers into Indonesia is one of the impacts of foreign investment in Indonesia to assist national development. The opportunity to utilize foreign workers (TKA) has significant impacts, both positive and negative impacts. By applying a normative judicial approach, this research is conducted to analyze the regulations to get license in hiring foreign workers and the law enforcement if there is any offense. Besides improving the investment climate, the philosophy of hiring foreign workers is to transfer knowledge from foreign workers to Indonesian workers. This research shows that the regulations to get license in hiring foreign workers are currently easier than the previous regulations. On the other hand, supervision regarding offesenses of permits to employ foreign workers has so far not been optimal.The government is expected to pay attention to the opportunities for Indonesian Citizens to get a job and take decisive action if there is any offense.